Effect of Macromolecular Crowders on the Self‐Assembly Process of Silk Fibroin. Issue 16 (19th July 2020) - Dubey, Priyanka; Seit, Sinchan; Chowdhury, Pramit K.; Ghosh, Sourabh
Abstract: Macromolecular crowding is known to have a significant impact on the aggregation and folding of proteins. In this study, the role of different macromolecular crowders such as polyethylene glycol (PEG 200 and PEG 6000) and dextran (dextran 6000 and 70000) on the self‐assembly of silk fibroin protein is explored. The data show that crowders induce a clear transition from random coil to β‐sheet secondary conformation in the fibroin as demonstrated by ThT fluorescence spectroscopy, circular dichroism, and ATR‐FTIR findings. However, this transition is not observed in case of control sample (fibroin without crowders). Excluded volume effects accelerate the kinetics of self‐association of the fibroin protein. Increasing the molecular weight of crowders increases the required time for maximum aggregation. This study suggests that treating the fibroin with different macromolecular crowders has modulated the propensity of fibroin going into β‐sheet conformation. Abstract : Macromolecular crowders are known to have a significant influence on various biochemical process, viz. protein folding, protein aggregation, and conformational transitions by mimicking the in vivo molecular confinement conditions in vitro. Based on this, different macromolecular crowders are used in the current study for modulating the self‐assembly process of silk fibroin in order to fabricate the biomaterials and scaffolds.